Thirteen-Year Sequelae of Marburg Virus Disease Survival: Persistent Cardiometabolic, Immunometabolic, and Haematological Alterations in the Absence of Psychological Morbidity - Jennifer Serwanga; Raymond Ernest Kaweesa; Joseph Katende Ssebwana; Goeffrey Odoch; Raymond Reuel Wayesu; Anne Daphine Ntabadde; Deborah Mukisa; Peter Ejou; FiloStudy Team; Julius Julian Lutwama; Pontiano Kaleebu (Pathogens, 2025)
Background: Marburg virus disease (MVD) is a highly lethal filoviral infection, yet its long-term health consequences remain poorly understood. We present one of the most temporally distant evaluations of MVD survivors, conducted 13 years post-outbreak in Uganda, offering novel insights into chronic physiological, biochemical, haematological, and psychosocial outcomes. Methods: A cross-sectional, community-based study compared ten MVD survivors with nineteen age- and sex-matched unexposed controls. Clinical evaluations included vital signs, anthropometry, mental health screening, and symptom reporting. Laboratory analyses covered electrolytes, inflammatory markers, renal and liver function tests, haematology, and urinalysis. Standardised psychological assessments measured anxiety, depression, perceived stigma, and social support. Findings: Survivors exhibited an elevated body mass index (BMI), higher systolic and diastolic blood pressure, and lower respiratory rates compared to controls, indicating ongoing cardiometabolic and autonomic changes. These trends may reflect persistent cardiometabolic stress and potential alterations in autonomic regulation, warranting further investigation. Biochemically, survivors exhibited disruptions in serum chloride, bilirubin, and total protein levels, suggesting subclinical hepatic and renal stress. Haematological analysis revealed persistent reticulocytosis despite normal haemoglobin levels, indicating long-term erythropoietic modulation. Despite these physiological changes, survivors reported minimal psychological morbidity, sharply contrasting with the post-recovery profiles of other viral haemorrhagic fevers. Stigma was prevalent during the outbreak; however, strong family support alleviated long-term psychosocial distress. Interpretation: Thirteen years post-infection, MVD survivors demonstrate multisystem physiological perturbations without marked psychological sequelae. These findings challenge assumptions of universal post-viral trauma and highlight the necessity for tailored survivor care models. Future longitudinal studies should investigate the mechanistic pathways underlying cardiometabolic and haematological reprogramming to inform intervention strategies in resource-limited settings.